Performance of High-Permittivity Ceramic-Polymer Composite as a Substrate for UHF RFID Tag Antennas. (3rd June 2012) - Babar, A. A.; Bhagavati, V. A.; Ukkonen, L.; Elsherbeni, A. Z.; Kallio, P.; Sydänheimo, L.
Abstract : A high-permittivity ceramic-polymer composite substrate is fabricated and proposed for its potential use in UHF RFID tags. The substrate is developed using high-permittivity Barium Titanate (BaTiO3 ) ceramic powder mixed with polydimethylsiloxane (PDMS) polymer. The resulting composite achieves a soft, hydrophobic, heat resistant, low loss, and flexible material with high dielectric constant. The percentage of the ceramic powder in the composite helps in achieving variable permittivity values. When this material is used as a substrate for a tag antenna, it will help the tag to be reduced in size, to conform to uneven or rough surface, and to be less vulnerable to breakage or other environmental damages. A small passive UHF RFID tag antenna is designed, fabricated, and attached to this type of composite substrate, to demonstrate the performance of this composite material.